A Nomogram to Identify Hyperkalemia Risk in Patients with Advanced CKD. Issue 10 (27th October 2022) - Xue, Cheng; Zhou, Chenchen; Yang, Bo; Ye, Xiaofei; Xu, Jing; Lu, Yunhui; Hu, Xiaohua; Chen, Jia; Luo, Xiaoling; Zhang, Liming; Mei, Changlin; Mao, Zhiguo
Key Points: Tools for diagnosis or prediction of hyperkalemia in CKD are limited, especially in patients not using RAASi. This study constructed a convenient nomogram and online calculator to identify the risk of hyperkalemia within 6 months in patients with advanced CKD. Patients with CKD who are identified as high risk of hyperkalemia by the tool may benefit from intensive monitoring and early triage. Visual Abstract: Abstract : Background: Hyperkalemia is a common and life-threatening complication of CKD. We aimed to develop and validate a nomogram that could identify the risk of hyperkalemia (≥5.5 mmol/L) in patients with CKD. Methods: A retrospective cohort study was performed in adult patients with predialysis advanced CKD (stages ≥3) in 2020–2021 for the outcome of hyperkalemia within 6 months. The training set was used to identify risk factors of hyperkalemia. Then a nomogram was developed by multivariable logistic regression analysis. C-statistics, calibration curves, and decision curve analysis (DCA) were used, and the model was validated in the internal and two external validation sets. Results: In total, 847 patients with advanced CKD were included. In 6 months, 28% of patients had hyperkalemia (234 out of 847). Independent risk factors were: age ≥75 years, higher CKD stages, previous event of serum potassium ≥5.0 mmol/L within 3 months, and comorbidities with heart failure, diabetes, or metabolic acidosis. Then the nomogram on the basis of the risk factors adding the use of renin-angiotensin-aldosterone system inhibitors was constructed. The C-statistic of the model was 0.76 (95% CI, 0.70 to 0.78), and was stable in both the internal validation set (0.73; 95% CI, 0.63 to 0.82) and external validation sets (0.88; 95% CI, 0.84 to 0.95 and 0.82; 95% CI, 0.72 to 0.92). Calibration curves and DCA analysis both found good performances of the nomogram. Conclusion: A feasible nomogram and online calculator were developed and validated to evaluate the risk of hyperkalemia within 6 months in patients with advanced CKD. Patients with CKD and a high risk of hyperkalemia may benefit from intensive monitoring and early triage.